PERCEPTION IN VIRTUAL REALTY ENVIROMENT - Kayapa, Nihal; Tong, Togan (YILDIZ TECHNICAL UNIV, 2011)
Recently, virtual reality environments also started to be used as representation tool by designers. Virtual reality differs from other representation tools especially because of the opportunities offered in depth source. Real world has three dimensions. Depth perception is the visual perception of the third dimension of the real world. Depth perception is created with information from the depth sources. These are ocular, stereoscopic, dynamic and pictorial information. The representation tools used frequently has only pictorial information. But the virtual reality comes over this disadvantage with some tools and hardware. In this environment, the spatial ideas are perceived with information from stereoscopic, dynamic and pictorial sources. Location and the depth of the objects in the real environment are perceived with information from allocentric and egocentric frames. Observer perceives both information from allocentric and egocentric frames in virtual reality like in real environment. Because of these factors, virtual reality provides a closer perceptual knowledge to real environments than the other representation tools. But there is not a single perceptual knowledge in virtual reality environment like real environment. Six main components are needed in order to create a virtual reality environment. These are model, computer programs, computer, tracking tools and interaction tool. These components can be defined in different ways and this, changes structure of the virtual reality and also, the perception of the environment. Virtual reality components also affect the properties of the environment. Three-dimensional graphical world, being immersed, interactivity and sensorial feedback are the properties of virtual reality. Being immersed is more important property than the others in the virtual reality used in design activity. Results of studies conducted on perceptual differences between real and virtual reality show that the perceptual responses in virtual reality environments with higher degree of being immersed are closer to real- world reaction. The factors, that increase the degrees of being immersed to virtual reality, are known. There are individual differences in the perceptual responses of observes and the relation between these factors and individual experience is unknown.
Keywords: Virtual reality environment; perceptional differences; being immersed; virtual reality components; Engineering